Baseline Sensitivity and Toxicity Mechanisms of Prochloraz to Alternaria alternata Strains Associated with Maize Leaf Blight in Heilongjiang Province in China - Shen, Guijin (Plant disease, 2024)
Alternaria species are fungal pathogens that can infect maize, causing leaf blight disease and significant economic losses. This study aimed to determine the baseline sensitivity to prochloraz of A. alternata isolates obtained from diseased maize leaves collected from Heilongjiang Province by assessing the half-maximal effective concentration (EC50) values. The EC50 values of prochloraz ranged from 0.0550 to 2.3258 μg/ml, with an average of 0.9995 ± 0.5192 μg/ml. At EC50 (1.2495 μg/ml) and 2EC50 (2.4990 μg/ml), prochloraz increased the number of mycelial offshoots, disrupted the cell membrane integrity of conidia and mycelia, and resulted in a reduced ergosterol content in the mycelia. Prochloraz significantly affected the mycelial cell membrane permeability and increased the malondialdehyde content and superoxide dismutase activity. No cross-resistance was detected between prochloraz and other fungicides. These data demonstrate that prochloraz is a promising fungicide for managing maize leaf blight caused by A. alternata and provide novel insights into understanding the mechanism of prochloraz toxicity against A. alternata isolates